TOAD handbook - Scalzo, Bert (Developer's library., 2010)
TOAD ® Handbook, Second Edition, is the definitive, completely up-to-date guide to the newest version of TOAD, the world's premier third-party Oracle utility. Packed with step-by-step recipes, screen snapshots, and hands-on exercises, this book brings together everything developers and DBAs need to maximize their productivity with TOAD in both administrative and development tasks. TOAD product architect Bert Scalzo and leading TOAD trainer Dan Hotka thoroughly cover every area of TOAD's functionality, offering practical, proven solutions that can be applied immediately to leverage TOAD's dramatically improved feature set. Comprehensive coverage includes TOAD setup and configuration Browsing databases and schemas Editing SQL and PL/SQL within TOAD Creating new databases Checking database health Performing common DBA tasks Reporting via standard and custom reports Optimizing database performance Throughout the text, the authors offer practical insights into each of TOAD's most useful tools, from App Designer to Doc Generator, ER Diagrammer to Code Road Map. This book is the only current, comprehensive, and affordable guide to the latest version of TOAD-a must-have for any TOAD user.